On the Benefits of a Symmetric Redox Flow Battery. Issue 3 (1st January 2016) - Potash, Rebecca A.; McKone, James R.; Conte, Sean; Abruña, Héctor D.
Abstract : Redox flow batteries (RFBs) are of interest for large-scale energy storage, but implementation has been challenged by their low energy density, high complexity, high cost, and insufficient lifetime due to several types of irreversible losses in the electrolyte. To address the issue of system complexity and irreversible losses, we have undertaken a detailed analysis of the concept of the symmetric redox flow battery, or SRFB, which relies on a single parent molecule as the charge storage species in both the positive and negative electrode reactions. Herein we elaborate on the operating principles and advantages of a SRFB and report the salient electrochemical properties of a class of organic molecules, diaminoanthraquinones (DAAQs) as promising candidates for use in SRFB redox electrolytes. Modeling of various modes of operation for SRFBs are presented along with an example of an operational, lab-scale SRFB based on a DAAQ system.